2011
DOI: 10.1007/s10803-011-1426-3
|View full text |Cite
|
Sign up to set email alerts
|

Specialized Inpatient Psychiatry Units for Children with Autism and Developmental Disorders: A United States Survey

Abstract: A cross sectional survey was performed to obtain the characteristics of specialized inpatient psychiatry units exclusively serving children with autism and other developmental disorders in the United States. Identified units were surveyed on basic demographic characteristics, clinical challenges and therapeutic modalities. Average length of stay was 42.3 days, children with autism spectrum disorders constituted the majority of the inpatient population (62.5-87.5%), and obtaining adequate post-discharge service… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 7 publications
2
34
1
2
Order By: Relevance
“…The high prevalence of ASD patients in the NSC inpatient program (76.9%), similar to that reported by other specialty inpatient programs (62.5–87.5%) [18], indicates there is a demand for such services.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The high prevalence of ASD patients in the NSC inpatient program (76.9%), similar to that reported by other specialty inpatient programs (62.5–87.5%) [18], indicates there is a demand for such services.…”
Section: Discussionsupporting
confidence: 74%
“…A recent survey-based study found only nine ASD/ID specialty inpatient psychiatric programs, all geographically limited to the northeast [18]. Results from that study suggest that there has been an increase in the number of these specialized inpatient programs developed within the past 10 years.…”
Section: Introductionmentioning
confidence: 99%
“…Integration of research into specialized inpatient psychiatry units that serve a high volume of children with ASD and other developmental disorders is one way to access large numbers of children with ASD and limited verbal ability. 92 Treatment development studies related to ER should also include participants representing the full range of verbal and cognitive abilities.…”
Section: Discussionmentioning
confidence: 99%
“…Despite their apparent increased vulnerability to developing serious problem behaviors (Kanne & Mazurek, 2011), those more severely affected by ASD are underrepresented in intervention research [Stedman, Taylor, Erard, Peura, & Siegel, ]. Furthermore, it is common for this subpopulation to require high levels of intensive intervention (e.g., specialized school placements, psychopharmacology, and in‐home behavioral therapies), which often exceed what providers in community settings can offer [Joshi et al, ; Siegel et al, ]. It can also land individuals with ASD in emergency rooms that are ill‐equipped to handle them [Hoffmann, Stack, Monuteaux, Levin, & Lee, ] and necessitate costly psychiatric hospital care [Croen, Najjar, Ray, Lotspeich, & Bernal, ; Nayfack et al, ; Siegel & Gabriels, ].…”
Section: Discussionmentioning
confidence: 99%